ALIRAN PEMIKIRAN KEISLAMAN JABARIYAH DAN QADARIYAH (Latar Belakang, Tokoh-Tokoh & Pokok Ajarannya) - widia fitria ningsi damang; Santalia, Indo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This discussion regarding Qadariyah and Jabariyah is very important considering that Qadariyah and Jabariyah are considered as an understanding of one problem, not as a school with various specific discussion themes and discussion methods. The purpose of this discussion is to find out the meaning, background and main points of Jabariyah and Qadariyah teachings. This research is a literature review research. The results of this research are that Jabariyah is a group that believes in the inability of humans to carry out any activity, and that all actions they have taken are nothing but decrees from Allah SWT, while Qadariyah is a group that rejects qadar (God's decree), namely a group that does not believe in There is God's decree for all affairs/cases. Jabariyah emerged since the time of the Companions and the Umayyad era. Meanwhile, the emergence of the qadariyah was motivated as a signal against the political policies of the Umayyads.